Gender-based Morphometric Analysis of the Human Orbital Aperture Profile using 3D Reconstruction Computed Tomography: A Cross-sectional Retrospective Study - Muhammad Omer Afzal Bhatti; Mujeeb Ur Rehman Parrey; Muhammad Ikram Ali; Allah Rakhyo Shoro; Abdulkrem Ahmed Alenazi; Rayan Alhumaidi Alruwaili (Journal of Clinical and Diagnostic Research)
Introduction: Sex estimation is a crucial aspect of forensic medicine and requires primary consideration when examining skeletal remains. Among the various anatomical features, the orbital region holds significant importance due to its distinct morphological variations. These variations provide valuable insights for sex determination, making orbital anatomy an indispensable tool in forensic investigations and analysis. Aim: To measure and compare orbital apertures between males and females using 3D Computed Tomography (CT) in a sample from the Saudi population. Materials and Methods: A cross-sectional retrospective study was conducted from January to June 2024 in the Radiology Department of Tower Hospital, Arar, Kingdom of Saudi Arabia, following the acquisition of ethical approval from the Local Bioethics Committee at Northern Border University. A total of 100 CT scans were randomly selected from the available dataset. The study encompassed CT scans of subjects from both genders, aged 18 years and above. However, CT scans of patients who had sustained head trauma or orbital injuries were excluded from the study. The data retrieved were analysed using Statistical Package for the Social Sciences (SPSS) version 23.0. All continuous data were tested for normality and expressed as Mean±Standard deviation (SD). The significant differences in orbital measurements between males and females were assessed using the Independent t-test. A p-value of <0.05 was considered statistically significant. Results: A total of 100 participants were included in the study, with the majority being females (52%). The mean age of male and female subjects was 40.5±13.19 years and 39.13±13.10 years, respectively. A statistically significant difference was found in right orbital width (p-value=0.011), left orbital area (p-value=0.04), and Interzygomatic Distance (IZD), with these measurements being higher in males compared to females (p-value=0.009). Conclusion: The study revealed that males have greater orbital width, orbital area and IZD compared to females. These gender-specific variations in orbital and facial dimensions may play a crucial role in gender determination within forensic medicine.